SIFAT PAPAN PARTIKEL DARI KULIT POHON GALAM (Melaleuca leucadendra) DENGAN PEREKAT UREA FORMALDEHIDA - Djoko Purwanto (BRIN Publishing, 2015)
Galam wood (Melaleuca leucadendra L.) is traditionally used for building materials, charcoal and fire wood. Currently, the tree bark remains unused, wasted or burned. The tree bark is potentially developed for particleboard manufacture. This paper studies the properties of particleboard made of galam tree bark. Galam bark pieces with dimension of 2 × 4 × 6 cm were bonded with Urea Formaldehyde (UF) in three different amounts: 11%, 13% and 15% of the total weight. The mixture was hydraulically pressed in 15 kg/cm² and temperatures of 110-120°C for 15 minutes prior to air dry. The physical and mechanical properties were tested according to the Indonesian National Standard 03-2105-2006. Results show that moisture content of the boards vary between 9.5 - 12.30% and the thickness swelling ranges between 2 - 11.35%. Boards density are about 0.68 - 0.77 g/cm³, Modulus of Elasticity (MOE) of 204.98 - 11210.91 kg/cm² and Modulus of Rupture ranges between 40.49 - 104.23 kg/cm². The screw withdrawal strengths are 44 - 84 kg and internal bond varies from 0.27 - 0.65 kg/cm². Based on the physical and mechanical properties, the particleboard made of galam tree bark mixed with 15% of UF meet the Indonesian National Standards 03-2105-2006.